The Shadow Economy An International Survey. (Cambridge Univ Pr, 2007)
"Illicit work, social security fraud, economic crime, and other shadow economy activities are fast becoming an international problem. Friedrich Schneider and Dominik H. Enste use currency demand, physical input (electricity) method, and the model approach, to estimate the size of the shadow economy in seventy-six developing, transition, and OECD countries. They argue that during the 1990s the average size of a shadow economy varied from 12% of GDP for OECD, to 23% for transition, and to 39% for developing countries. They examine the causes and consequences of this development using an integrated approach explaining deviant behaviour, which combines the findings of economic, sociological, and psychological research. The authors suggest that increasing taxation, social security contributions, rising state regulatory activities, and the decline of the tax morale, are all driving forces behind this growth, especially in OECD countries. They propose a reform of state (public) institutions, in order to improve the dynamics of the official economy."--Jacket
Keywords: Informal sector (Economics); Business enterprises -- Corrupt practices; Commercial crimes; Tax evasion; Noncitizens; Welfare fraud; Fraud; Illegal immigration; Fraud